PELAKSANAAN PERJANJIAN POLA KREDIT KOPERASI PRIMER ANGGOTA (KKPA) DI PT. KTU ASTRA YANG DIKELOLA OLEH KOPERASI RIMBA MUTIARA - Yudhi Fasrah Ilahi; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The agreement is a legal relationship regarding property between two parties, in which one partypromises or is considered promising to do something or not. The main issues discussed in this paper areregarding agreements or provisions made by cooperatives in RAT number 15 / KOP-RM / TR / X / 11deciding in the second part namely To Participant Farmers who have been determined, Prohibited fromSelling Buy Palm Oil Plantation Land ( KKPA). Violated or Not implemented by members of the pearljungle cooperative in Siak district, Koto Gasip district.The research method used is empirical research, another term used is Sociological legal researchalso called field research and this research is descriptive. In data collection, the types of data used in thisstudy are primary data and secondary data, namely directly through respondents (field), Law Number 18Year 2004 concerning Plantation, Civil Code, legal journals and books - books related to research. Analysisof this data is done qualitatively and deductively drawn conclusions.From the results of research conducted by the author, it was found that there were still farmers whowere members of the KKPA who sold their oil palm plantation to other parties. So that the regulationNumber: 15 / KOP-RM / TR // 11 in deciding sets out the second part: "to the participating farmers whohave been determined, it is prohibited to trade in the palm oil." Not applicable.So that based on this matter, strict sanctions are needed, be it administrative sanctions or criminalsanctions for parties to carry out the buying and selling process so that regulations made by cooperativescan be enforced.Keywords : Agreement, cooperatives and farmers of KKPA members